﻿Frequency of CYP2D6*3 and *4 and metabolizer phenotypes in three mestizo Peruvian populations - Angel T. Alvarado; Roberto Ybañez-Julca; Ana María Muñoz; César Tejada-Bechi; Roberto Cerro; Luis Abel Quiñones; Nelson Varela; César André Alvarado; Erick Alvarado; María R. Bendezú; Jorge A. García (Pensoft Publishers, 2021)
Wild type genotypes (CYP2D6) and their allelic variants have been described in a sample of a Peruvian mestizo population. The global allele frequency was 0.015 for CYP2D6*3 and 0.051 for CYP2D6*4. The percentages of genotypes described were 97% CYP2D6*1/*1 and 3.0% CYP2D6*1/*3; 90.60% for CYP2D6*1/*1, 8.55% CYP2D6*1/*4 and 0.85% CYP2D6*4/*4. The allelic frequencies of CYP2D6*3 in the Lima subpopulations were 0.022 and 0.010 for Junin; CYP2D6*4 of 0.048, 0.060, and 0.050 for residents of Lima, Junín, and Tacna, respectively. The Hardy-Weinberg equilibrium test for the studied population showed that both frequencies are in equilibrium, p <.05. The metabolizer phenotype was inferred according to the genotypes: 11.54% were classified as intermediate metabolizers (*1/*3 or *1/*4) and 0.85% as poor metabolizers (*4/*4). It is concluded that the frequencies of the CYP2D6*3 and CYP2D6*4 alleles are low for the Peruvian mestizo population compared to the Latin American and tricontinental population, due to their natural population evolution, which is manifested by their decreased metabolic activity, the same that is relevant in clinical practice.